Dehydration: Need For an Improved Rehydrating Energy Drink - Faruqui, Arif A. (Jurnal Ilmu Kesehatan Indonesia, 2023)
Oral rehydration therapy (ORT) is the cornerstone treatment for managing dehydration. However, ORT cannot “halt” the underlying intestinal fluid loss, a significant mechanism of infectious organisms responsible for causing diarrhea. Reports have demonstrated the role of calcium in treating contagious diarrhea through the calcium-sensing receptor (CaSR), which is absent in oral rehydration solution (ORS). CaSR is a novel target that has demonstrated its effectiveness in treating diarrhea. CaSR is activated by a simple calcium agonist, an easily accessible, inexpensive, and safe-to-use option in the pediatric population. Adding nutrients would be simple and may increase the efficacy of the current ORS treatment. Maltodextrin (MDs) over glucose in ORS has shown benefits in these patients as the osmolality of MDs is significantly lower than that of disaccharide sugars. Thus, adding multivitamins, nutrients, and energy boosters to WHO- ORS may improve the efficacy of ORS in treating diarrhea, reducing malnutrition, and providing energy to curb fatigue.